Long-term effect of copper and tetracycline on the performance and sludge characteristics of anoxic-aerobic sequencing batch reactor with integrated sludge disintegration - Gurtekin, Engin (Elsevier Science Inc, 2023)
In this study, it was aimed to determine the change in the toxic effect of copper (Cu2+) and tetracycline (TC) on biological treatment by sludge disintegration application. For this purpose, two labscale reactors, sequencing batch reactor (SBR) and sludge disintegration applied sequencing batch reactor (SBR-SD), were used. In the control stage of SBR and SBR-SD, namely SBR-C and SBR-SD-C, the chemical oxygen demand (COD) and NH4+-N removal efficiency was 93% and 95%, respectively. While reductions were observed in the COD and NH4+-N removal efficiency from the 66th day in SBR, stable treatment efficiency was obtained in SBR-SD throughout the operation. While sludge volume index value increased to 175 mL/g in SBR, it remained stable between 78-85 mL/g in SBR-SD. While the decrease in the specific oxygen consumption rate value in SBR was 55% on the 90th day due to the toxicity of Cu2+ and TC, it was 29% in SBR-SD. In SBR, PN and PS content in tightly bound extracellular polymeric substances (TB-EPS) and loosely bound extracellular polymeric substances (LB-EPS) increased due to resistance to the toxic effects of Cu2+ and TC. The protein (PN) and polysaccharide (PS) content in TB-EPS and LB-EPS remained the same as the control stage values since the toxic effect of Cu2+ and TC in SBR-SD was relatively eliminated by sludge disintegration. The toxic effect of Cu2+ and TC on biological treatment was prevented by sludge disintegration and stability was ensured during long-term operation.
Keywords: Copper; Tetracycline; Sequencing batch reactor; Sludge disintegration